Male but not female zebra finches with high plasma corticosterone have lower survival. (11th December 2017) - Jimeno, Blanca; Briga, Michael; Hau, Michaela; Verhulst, Simon
Abstract: The glucocorticoid axis is essential for coping with predictable and unpredictable environmental variation. Despite this vital function, attempts to link individual variation in the glucocorticoid axis to survival have yielded mixed results, which may be due to endocrine variation caused by uncontrolled variation in environment and life‐history traits such as reproductive effort. We therefore studied the link between the glucocorticoid axis and long‐term survival using captive non‐breeding zebra finches. We quantified the relationship between survival over a three‐year period and plasma corticosterone concentrations: (1) baseline, (2) stress‐induced, (3) after induction of negative feedback via dexamethasone injection and (4) after maximal adrenal stimulation via adrenocorticotropin hormone injection. Only stress‐induced corticosterone predicted survival, with higher concentrations being associated with lower survival. However, this effect differed significantly between the sexes, being present only in males. Stress‐induced corticosterone concentration is the sum of baseline corticosterone and the corticosterone increase in response to the standardized stressor, and both components were similarly associated with male survival in a model that included both variables. This implies that baseline corticosterone itself also exerts an effect on male survival, but this was only revealed when the stress‐induced corticosterone increase was included in the model, presumably because this increased statistical power. Given that corticosterone concentrations are highly repeatable in our study population and independent of manipulated foraging conditions, these data suggest that endocrine stress reactivity may be a major component determining male life span, presumably also in wild populations. A plain language summary is available for this article. Abstract : Plain Language Summary